What was Reconstruction? - Smith, Sherri L.; Foley, Tim (New York : Penguin Workshop, 2022)
"Reconstruction -- the period after the Civil War -- was meant to give newly freed Black people the same rights as white people. And indeed there were monumental changes once slavery ended -- thriving new Black communities, the first Black members in Congress, and a new sense of dignity for many Black Americans. But this time of hope didn't last long and instead, a deeply segregated United States continued on for another hundred years. Find out what went wrong in this fascinating overview of a troubled time"--Provided by publisher
Legacy
Includes bibliographical references (pages 108).
Keywords: Reconstruction (U.S. history, 1865-1877) -- Juvenile literature; African Americans -- History -- 1863-1877 -- Juvenile literature